How to Improved MSMEs Competitiveness in Indonesia?: Augmented Reality for Digital Marketing Innovation - Situmorang, Robinson; Kustandi, Cecep; Khaerudin (JTP - Jurnal Teknologi Pendidikan, 2024)
This research aims to analyze the development of Augmented Reality (AR) as a digital marketing innovation in tourist villages in West Java. This research uses the Borg and Gall (2003) development model with quantitative and qualitative data analysis techniques. The research results show that this mobile-based AR is said to be feasible for use with an average feasibility test value of 78.7%. The implication of this research is tourist villages in promoting their tourism potential starting from tourist destinations to MSMEs. Apart from that, the presence of MSMEs can also encourage the potential of culinary tourism in tourist villages so that they can develop further following technological developments.